An Analysis of Metaphor in Elemental (2023) Movie - Fitrianingtyas, Devi Nur Alif; Harida, Ratri; Putra, Tomy Kartika (SALIENCE: English Language, Literature, and Education Journal, 2025)
Metaphors in the movies often serve to deepen the narrative or highlight themes. The research aims to find out the types and meanings of metaphors used in Elemental Movie. The research applied the descriptive qualitative method and follows the interactive analysis model by Miles and Huberman, which included data collection, reduction, display, and conclusion. Based on data analysis conducted on Elemental Movie, it contains 30 expressions from forty types of metaphor according to Ullmann’s theory; those types of metaphor consist of concrete to abstract metaphors (40%), followed by anthropomorphic metaphors (33%), synesthetic metaphors (20%), and animal metaphors (7%). Based on the findings, the writer concludes that the type of metaphor that moves from abstract to concrete is the most frequently used in Elemental. It becomes the most frequently used metaphor since it has a crucial role across various media by making complex ideas more accessible through tangible experiences. The study suggests that English students and those interested in semantics should analyze metaphors in movies to deepen their understanding of metaphorical language.